Passages - Quin, Ann 1936-1973 (British literature series, 2003)
"Two characters - a woman in search of her brother, and the woman's lover in search of himself - travel the Mediterranean landscape, co-dependently bound to one another in a hopeless relationship." "Mirroring the schizophrenic nature of the characters, the text is broken up into alternating sections of narrative and diary entries. The lyrical nature of the prose counters this fragmentation, as resonances develop amid "cut-up" dreams and fantasies in a fashion similar to a musical composition."--BOOK JACKET.